Pemberlakuan Aturan Hukum Pajak Terhadap Youtuber dan Penjual Online Shop - Shahrullah, Rina Shahriyani; Syarief, Elza; Crystina, Aprillia (Journal of Law and Policy Transformation, 2019)
Under Article 4, Section 1 of Income Tax Law No 36 of 2008 explicitly stated that income is the object of taxation. The income referred to is any additional economic ability that is obtained or received by the taxpayer with the intent to consume or improve the value of the taxpayer itself. Therefore, all income received by Youtuber or Online Shop Merchants needs to be taxed. The research has a purpose to find out which law that rules Youtuber and Online Shop Merchants especially in a field that concerns income tax. The experiment also reviews which sanction can be applied to Youtuber and Online Shop Merchant should they violate the law. This legal research is in normative form using both the legal approach and analysis approach towards legal concepts or theories. The theories used are the theory of justice and the theory of legal certainty. As for the legal substance, a secondary substance in a form of written laws and regulations as well as research results regarding the issue. Based on the result of this research, the law governing Youtubers and Online Shop Merchants are mentioned in Republic of Indonesia Ministry of Finance Regulation No 210/PMK.010/2018 about laws regarding Tax Application and Trade Transactions through e-commerce with a punishment of administrative sanction or criminal sanction should violation or breach of law occurs.